¿Son los ácidos grasos de la carne y la leche bovina nocivos para la salud de las personas? - Rodrigo Arias (Revista Chilena de Nutrición, 2016)
Nutritional recommendations of the past 35-40 years have promoted the reduction of fat intake, calories and particularly saturated fatty acids (SFA), emphasizing lower consumption of red meat and high fat dairy products, because of its association with cardiovascular diseases (CVD), being in turn replaced by sugars and refined carbohydrates. There is consensus that the SFA concentration in blood plasma, particularly palmitic acid, are associated with an increased risk of CVD and heart attacks. However, there is no evidence of causality between CVD and consumption of SFA, raising reasonable doubts about the relationship between consumption of SFA with those present in blood plasma, as well as with the CVD risk. This review presents scientific evidence that demonstrates that the inclusion of fats in the diet, specifically animal fats from ruminants, provide important health benefits for people, especially when accompanied by a reduction in the consumption of carbohydrates. It is also proposed that ruminant products and their fatty acids contribute with beneficial saturated fats for people´s health, especially those from pastoral production systems such as vaccenic, rumenic and linolenic acids.